TEACHING EFFECTIVENESS IN TECHNOLOGY-MEDIATED DISTANCE LEARNING. - WEBSTER, J.; HACKLEY, P. (Academy of Management Journal, 1997)
Technology-mediated distance learning is becoming increasingly important to business curricula. However, little theoretical development or empirical research has examined teaching effectiveness in ...